RI 9231 - In Situ Measurements and Preliminary Design Analysis for Deep Mine Shafts in Highly Stressed Rock - M. P. Board (The National Institute for Occupational Safety and Health (NIOSH), 1989)
The U.S. Bureau of Mines, under a cooperative agreement with Hecla Mining Co., conducted a rock mechanics study at four widely spaced horizons in a deep mine shaft in northern Idaho. The objective of the project was to measure and analyze rock deformation and lining behavior during construction of a deep shaft in a high in situ stress field within an isotropic rock mass. Rock mass displacements were monitored with multiple-position borehole extensometers. Liner stress and strain were measured with concrete pressure cells and embedment strain gauges. This report discusses the general trends and magnitudes of data from the four test sites, and relates the data to a proposed anisotropic constitutive model for the rock mass. A design procedure is then outlined for specifications of liner thickness and support installation sequences for future shaft sinking.